Oak Leaves as a Raw Material for the Production of Alcoholic Fermented Beverages - Pencak, Tomas; Dordevic, Dani; Ćavar Zeljković, Sanja; Tremlova, Bohuslava (Foods (Basel, Switzerland), 2024)
This study aimed to point out the possible use of oak leaves (Q. petraea) in the production of fermented alcoholic beverages. Parameters such as antioxidant capacity, total phenolic content, phenolics and sugars were determined using spectrophotometric and chromatographic methods. pH values were also determined, and in the final product with a fermentation length of 85 days, the alcohol content was determined and sensory analysis performed. The antioxidant capacity of the beverage was lower compared to the infusions before fermentation, and its highest values were recorded in the leaf samples, in which the highest values of phenolic compounds and the total phenolic content were also recorded. A decrease in the content of total phenolics was recorded with the increasing length of fermentation in beverage samples. However, the fermentation process had a positive effect on the contents of some phenolic substances such as catechin, gallic acid and gallocatechin. Sensory analysis showed a higher acceptability of the fermented beverage without the addition of orange, which could be caused by the higher sugar content in these samples. Oak leaves therefore represent a suitable raw material for the production of a fermented alcoholic beverage, without the need to enrich the taste with other ingredients.
Keywords: polyphenols; Quercus; fermentation; oak leaves; alcoholic beverages; antioxidant capacity